(untitled) (CaJoST, 2025)
The antioxidant potentials of five common medicinal plants (Foeniculum vulgare, Ocimum basilicum, Syzgium aromaticum, Lagenaria breviflora and Luffa cylindrical) were investigated. The Nitric oxide (NO) radical scavenging ability, 2, 2-diphenyl-1-1-picrylhydraxyl (DPPH) radical scavenging ability, hydroxyl radical scavenging ability, Ferric reducing antioxidant potential and total antioxidant capacity of the plants were determined using standard procedures. Of the five plants compared, L. breviflora gave the highest percentage (83.54±1.85%) hydroxyl radical scavenging effect and when compared to the standard antioxidant (Ascorbic acid) showed no significant difference. For the Nitric oxide and DPPH radical scavenging assays, the plant Foeniculum vulgare recorded the highest percentage. O. basilicum gave the best ferric reducing antioxidant power while for the total antioxidant capacity the plant Sygium aromaticum, gave the best scavenging effect. The study revealed that the five medicinal plants possesses a significant antioxidant potential that can be taken advantage of in combating diseases related to oxidative stress.